A Review of Hope in the Dark: Untold Histories, Wild Possibilities by Rebecca Solnit. - Julianne Burgess (Brock University, 2020)
Rebecca Solnit's book makes the case for hope as a commitment to social action in an uncertain world. The author draws from her own history of activism and her study of environmental, political and cultural history, to shine a light on long forgotten transformative victories. Solnit argues that we are living in a time of exciting, unprecedented social change.